Musculoskeletal disorders in New Zealand nurses: incidence, persistence/recurrence and impact on work and functional tasks. (7th October 2012) - Harcombe, H; McBride, D; Herbison, P; Derrett, S
Abstract : Background: Few prospective studies have investigated musculoskeletal disorders (MSDs) at a range of anatomical sites in nurses. Aims: To determine the cumulative incidence and persistence or recurrence of MSDs of the low back, neck, shoulder, elbow, wrist/hand and knee in a cohort of New Zealand nurses and to determine the prevalence of MSDs affecting work and functional tasks. Methods: Nurses (n=280) were randomly selected from the Nursing Council database and invited to participate in a postal survey at baseline and 12 months later. MSDs were identified based on self-reported pain at the anatomical site. MSDs affecting work involved either time off work or modified duties. Functional tasks were assessed at site-specific level. Results: The 12 month cumulative incidence of MSDs was highest for low back (35%), followed by neck (31%), shoulder (25%), wrist/hand (18%), knee (17%) and elbow (11%) pain. Depending on the anatomical site, 45–76% of MSDs were persistent or recurrent. The 1-month prevalence of MSDs affecting functional tasks was 14–20% for shoulder, wrist/hand, knee and low back pain. The 12-month prevalence of MSDs affecting work was highest for low back pain (20%) followed by shoulder pain (10%). Significance: To reduce MSDs among nurses attention appears warranted at a wider range of sites than the low back alone.